Molecular characterization and antibiotic resistance of Clostridioides difficile in patients with inflammatory bowel disease from two hospitals in China - Tao Lv; Lisi Zheng; Tao Wu; Ping Shen; Yunbo Chen (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: Objectives: Patients with inflammatory bowel disease (IBD) are susceptible to Clostridioides difficile infection (CDI), resulting in poor outcomes and recurrence; therefore, the molecular characterization of C. difficile in IBD patients in China needs further investigation. Methods: C. difficile strains were isolated and identified from faecal samples of adult and paediatric IBD patients. Toxigenic strains were typed using multilocus sequence typing and whole genomic sequencing (WGS) to construct the phylogenetic tree. Susceptibility to 10 antimicrobials was evaluated using the Etest. Results: Among the 838 IBD patients, 82 toxigenic C. difficile were identified, which comprised 46 from adults and 36 children. A total of 90.2% (74/82) of the isolates were positive for both toxin A and toxin B genes (A+B+), whereas the remaining 9.8% were negative for toxin A gene but positive for toxin B gene (A–B+). These toxigenic strains were susceptible to metronidazole and vancomycin, but highly resistant to clindamycin, erythromycin, and fluoroquinolones. All moxifloxacin-resistant isolates had mutations resulting in an amino acid substitution in gryA (T82I). The dominant types were ST-35 (20.7%), ST-2 (17.1%), ST-54 (13.4%), and ST-3 (13.4%) in all patients. Conclusion: The incidence and molecular epidemiology of C. difficile infection in adult IBD patients resembled CDI in the general inpatient population. A higher antibiotic resistance rate was identified among the C. difficile isolates obtained from paediatric IBD patients than from adult patients, and a few STs accounted for most multidrug-resistant strains. However, the molecular genetic features of the same ST type between these two groups remains highly correlated.